Caracterização e análise dos adornos funerários dos sítios Pedra da Tesoura e Lajedo do Cruzeiro, Paraíba – Brasil - Soares, Tatiane Maria (2020)
The funerary adornments identified at the sites Pedra da Tesoura - Boqueirão and Lajedo do Cruzeiro - Pocinhos, located in the state of Paraíba, provided significant evidence for the understanding of the funerary rituals developed by the peoples who inhabited the Cariri Paraibano region in past times. The two sites are framed as shelters-under-rock and are in an area of ethno-historical and historical influence of the Cariri people, according to the reports of chroniclers. The research was carried out at the Núcleo de Pesquisas e Estudos Arqueológicos e Históricos (NUPEAH UFAL/Delmiro Gouveia), at the Laboratório de Bioarqueologia (LABIARQ-UFS/Laranjeiras) and had the support by the Instituto Memorial da Borborema. This work aims to characterize and analyze the beads and pendants, using the technical and morphological variables, realizing if there was preference in the choices of raw material and other specificities used during the making, possible inter-site distinctions, contributing to the expansion of studies on adornments on a regional, national e international scale. In this research we present the results referring to the analyses carried out in a quantity of 251 funerary adornments, from two sites in the interior of Paraíba. The elements that represent contiguities in the two sites were the presence of bird bones and vegetable remains, as well as the use of different decoration patterns (geometric, dotted and cut marks on the ends). The shapes, dimensions and surface treatment were made operational in the adornments depending on the choice of the raw material, the stylistic preferences of the craftsman and the group. The elements that make up the divergences are associated with to the presence of adornaments made of different of different minerals, felids teeth, probably human teeth and some beads that did not have their raw material characterized, existing only in the sample of the Pedra da Tesoura site, also showing vegetable fibers manufactured goods (baskets and cordage).The sites had diversified secondary burials, but the bioturbations that occurred at the two sites did not allow the direct association of these traces to the individuals.